Effects of glycolysis and polyamine predation on intestinal epithelial barrier in colorectal cancer - Wang, Yu; He, Huan; Chen, Jingwen; Song, Zijing; Pan, Xuediao; Lan, Tian; Wang, Guixiang (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is the second most lethal cancer and the third most common cancer in the world, and its prognosis is severely affected by high intestinal mucosal permeability and increasing tumor burden. Studies have shown that the expression of hypoxia induce factor 1α (HIF1α) is up-regulated in a variety of tumor tissues, which is related to multiple metabolic reprogramming of tumor cells. However, the role of HIF1α in CRC tumor growth, tumor polyamine metabolism and intestinal mucosal barrier damage has not been studied. Here, we constructed different types of CRC tumor-bearing mice models by inoculating HCT116 cells with different levels of HIF1α expression (knockdown, wild type, overexpression) in the armpits of mice to explore the upstream and downstream regulators of HIF1α, the effects of HIF1α on the growth of CRC, and the CRC polyamine metabolism and its effect on the intestinal mucosal barrier. We found that with the increase of HIF1 gene expression, tumor growth was promoted and intestinal mucosal permeability was increased. HPLC showed that the polyamine content in the tumor tissue of the overexpression group (HIF1αOE) was higher than that of the wild group (HIF1α(+/+)), and higher than that of the knockdown group (HIF1α(-/-)), but the content of polyamines in intestinal mucosa was the opposite.The expression of glycolysis-related proteins was up-regulated, the rate-limiting enzyme ODC of polyamine synthesis was decreased, and the transfer protein of polyamine was increased. After supplementation of exogenous polyamines, the content of polyamines in intestinal mucosa and tumor tissue increased, and the damage of intestinal mucosa was alleviated. In conclusion, upon activation of the MYC/HIF1 pathway, tumor glycolysis is enhanced, tumors require more energy and endogenous polyamine synthesis is reduced. Therefore, in order to meet its growth needs, tumor will rob polyamines in the intestinal mucosa, resulting in intestinal mucosal epithelial barrier dysfunction.